An assessment of seasonal fluctuations in physicochemical variables in Lake Zuzuwadi and Lake Ballur of Hosur Dt., Tamil Nadu, India - Padmakumar, Vidya; S, Murugan (International journal of Rural Development, Environment and Health Research, 2022)
Seasonal changes in physicochemical characteristics were investigated in Zuzuwadi Lake and Ballur Lake in the Hosur District of Tamil Nadu, India. Throughout the year, mean air and water temperatures ranged from 27.0 to 32.0ºC. The dissolved oxygen concentrations at each station throughout the summer and winter seasons were in the range of 6.0 ± 0.113 (±1.89%) to 9.0 ± 1.118 (±1.57%) ppm and 12.0 ± 0.127 (±1.05%) to 13.5 ± 0.445 (±3.51%) ppm, correspondingly. The conductivity was between 300.0 ± 1.652 (±4.15%) to 329.0 ± 2.422 (±4.15%) µS/cm. The nitrate content of Lake Zuzuwadi ranges from 8.0 ± 0.113 (±1.62%) to 10.0 ± 1.132 (±12.57%) ppm, indicating that the water is oligotrophic and could destroy aquatic ecosystems. In Lake Zuzuwadi, the Biological Oxygen Demand and Chemical Oxygen Demand remained at 5.0 ± 0.113 (±1.62%) and 200.0 ± 12.652 (±4.15%) ppm, respectively, but in Lake Ballur, they were 9.0 ± 1.386 (±19.80%) and 200.0 ± 12.652 (±4.15%) ppm. Both stations had salinities of less than 200.0 ± 1.497 (±0.50%) ppm. Lake Zuzuwadi has been found to have algal blooms. According to the comparative Physico-chemical parameter interpretations, Lake Zuzuwadi is oligotrophic in nature, while Lake Ballur is slightly contaminated, containing a diverse array of aquatic creatures that rely on the lakes to exist. Zuzuwadi Lake had a WQI of 60.6 ± 0.999 (±1.65%), whereas Ballur Lake had a WQI of 70.4 ± 0.784 (±1.11%) indicating that the water quality is bad.